2013
DOI: 10.1149/2.051306jes
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Polymer Electrolyte Fuel Cell Operation at Sub-Freezing Temperatures

Abstract: The ability of polymer electrolyte fuel cells (PEFCs) to startup at subfreezing temperatures is governed by whether it is able to overcome the freezing point (0 • C) before product ice prevents the electrochemical reactions. In this work, we experimentally investigated the coulombs of charge Q c transferred in PEFCs under subfreezing operation before the output voltage drops to 0.0 V. PEFCs with various membranes and catalyst-layer thicknesses, ionomer-carbon ratios, operating current density, and initial hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…[39][40][41] The influence of operating parameters on fuel cell performance was shown through in situ total displacement and degree of deformation of the polymer membrane. 32 Numerical results of a cold-start simulations 42 concluded that it was better to increase the ionomer fraction in the cathode CL than to increase the thickness of the membrane in order to reduce ice formation. As ohmic heat is the largest heating source at low cell voltages, 43 a successful startup of the cell requires that temperatures above freezing be achieved before ice formation blocks the electrochemical reaction, inhibiting cell performance to a point where the cell can no longer generate sufficient heat.…”
Section: F1318mentioning
confidence: 99%
See 2 more Smart Citations
“…[39][40][41] The influence of operating parameters on fuel cell performance was shown through in situ total displacement and degree of deformation of the polymer membrane. 32 Numerical results of a cold-start simulations 42 concluded that it was better to increase the ionomer fraction in the cathode CL than to increase the thickness of the membrane in order to reduce ice formation. As ohmic heat is the largest heating source at low cell voltages, 43 a successful startup of the cell requires that temperatures above freezing be achieved before ice formation blocks the electrochemical reaction, inhibiting cell performance to a point where the cell can no longer generate sufficient heat.…”
Section: F1318mentioning
confidence: 99%
“…45,46 The use of a microporous layer (MPL) further expands the ice storage capacity of the electrode, 32 and a hydrophilic layer in the GDL that can absorb product water further enhancing FC performance by increasing the overall water holding capacity of the cell. 26 Some other cold-start strategies include potentiostatic startup, 47 purging the cell with dry gas, 48 or filling the cell compartments with an antifreeze solution before reducing the cell temperature below 0…”
Section: F1318mentioning
confidence: 99%
See 1 more Smart Citation
“…Mishler et al found only minor differences in water storage capacity between MEAs prepared with Nafion NR-211 and NR-212 (25.4 and 50.8 μm, respectively). 13 Tajiri et al found that for an initial water content between λ = 2 and λ = 4, negligible difference in water storage capacity was obtained for a single (30 μm) and double (60 μm) thickness GoreTex membrane with identical CLs. 36 Ionomer comparison.-The mobility and availability of non-frozen water within the hydrophilic portions of the ionomer decrease nonmonotonically with temperature.…”
Section: Resultsmentioning
confidence: 99%
“…; where e CL is the CL porosity, r ice is the ice density, and a is the net water transfer coefficient). 109,[193][194][195] Another critical issue under high current density is water and thermal management. Both waste heat and water generation increase with current density.…”
Section: Energy and Environmental Science Reviewmentioning
confidence: 99%